Relationships between photochemical reflectance index and light-use efficiency in deciduous and evergreen broadleaf forests (Remote Sensing of Environment, 2014)
In this study, we evaluate the relationships between the photochemical reflectance index (PRI) and light-use efficiency (LUE) based on eight years of continuous in situ measurements acquired on a half-hourly basis for PRI, NDVI (Normalized Difference Vegetation Index), the main micrometeorological variables and net CO2 exchange data in two deciduous and evergreen mature forests. More specifically, the objectives of this study include investigating the daily, seasonal, and interannual variations of PRI and LUE; linking PRI variations to the main influencing meteorological and eco-physiological variables; and evaluating the performance of PRI as a remote-sensing proxy of LUE under different environmental conditions. The data analysis was performed at different time scales within the season using moving temporal windows and between years. On a seasonal scale, statistical analyses revealed positive relationships between PRI and absorbed photosynthetically active radiation (aPAR) and negative relationships between PRI and LUE. Over shorter periods of a few days, the signs of these relationships remained unchanged; however, their correlations were strongly improved. The highest correlations were most often observed over periods characterized by clear or slightly overcast skies. However, all the periods of clear skies did not involve improvements in the relations of PRI vs. aPAR or PRI vs. LUE. Temporal variations of the intercept (called PRI0 in this study) of PRI vs. aPAR regressions suggest the presence of a temporal trend that may reflect seasonal changes of the biochemical characteristics of the canopy. Regardless of the cause of this trend, it is important to note that once PRI0 was subtracted from the measured PRI, the correlations between the corrected PRI and LUE for each year were significantly improved, and a stable multi-year model was obtained. Nevertheless, further studies are required to explain the temporal changes of PRI0 during the season and to develop a more accurate disentangling approach that would make PRI-based remote-sensing of ecosystem light-use efficiency less sensitive to confounding factors related to spatial and temporal changes in the structural and biochemical properties of the canopy.

Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M.; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M.; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

Quercus ilex recruitment in a drier world: A multi-stage demographic approach (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.

The temporal response to drought in a Mediterranean evergreen tree: comparing a regional precipitation gradient and a throughfall exclusion experiment - Martin-StPaul, Nicolas K.; Limousin, Jean-Marc; Vogt-Schilb, Helene; Rodriguez-Calcerrada, Jesus; Rambal, Serge; Longepierre, Damien; Misson, Laurent (GLOBAL CHANGE BIOLOGY, 2013)
Like many midlatitude ecosystems, Mediterranean forests will suffer longer and more intense droughts with the ongoing climate change. The responses to drought in long-lived trees differ depending on the time scale considered, and short-term responses are currently better understood than longer term acclimation. We assessed the temporal changes in trees facing a chronic reduction in water availability by comparing leaf-scale physiological traits, branch-scale hydraulic traits, and stand-scale biomass partitioning in the evergreen Quercus ilex across a regional precipitation gradient (long-term changes) and in a partial throughfall exclusion experiment (TEE, medium term changes). At the leaf scale, gas exchange, mass per unit area and nitrogen concentration showed homeostatic responses to drought as they did not change among the sites of the precipitation gradient or in the experimental treatments of the TEE. A similar homeostatic response was observed for the xylem vulnerability to cavitation at the branch scale. In contrast, the ratio of leaf area over sapwood area (LA/SA) in young branches exhibited a transient response to drought because it decreased in response to the TEE the first 4years of treatment, but did not change among the sites of the gradient. At the stand scale, leaf area index (LAI) decreased, and the ratios of stem SA to LAI and of fine root area to LAI both increased in trees subjected to throughfall exclusion and from the wettest to the driest site of the gradient. Taken together, these results suggest that acclimation to chronic drought in long-lived Q. ilex is mediated by changes in hydraulic allometry that shift progressively from low (branch) to high (stand) organizational levels, and act to maintain the leaf water potential within the range of xylem hydraulic function and leaf photosynthetic assimilation.
The following values have no corresponding Zotero field: pub-location: 111 RIVER ST, HOBOKEN 07030-5774, NJ USA publisher: WILEY-BLACKWELL
Keywords: allometry; carbon allocation; chronic stress; ecosystem manipulation; hydraulic adjustments; leaf ecophysiology; long-term drought; Quercus ilex; Water availability

The temporal response to drought in a Mediterranean evergreen tree: comparing a regional precipitation gradient and a throughfall exclusion experiment (GLOBAL CHANGE BIOLOGY, 2013)
Like many midlatitude ecosystems, Mediterranean forests will suffer longer and more intense droughts with the ongoing climate change. The responses to drought in long-lived trees differ depending on the time scale considered, and short-term responses are currently better understood than longer term acclimation. We assessed the temporal changes in trees facing a chronic reduction in water availability by comparing leaf-scale physiological traits, branch-scale hydraulic traits, and stand-scale biomass partitioning in the evergreen Quercus ilex across a regional precipitation gradient (long-term changes) and in a partial throughfall exclusion experiment (TEE, medium term changes). At the leaf scale, gas exchange, mass per unit area and nitrogen concentration showed homeostatic responses to drought as they did not change among the sites of the precipitation gradient or in the experimental treatments of the TEE. A similar homeostatic response was observed for the xylem vulnerability to cavitation at the branch scale. In contrast, the ratio of leaf area over sapwood area (LA/SA) in young branches exhibited a transient response to drought because it decreased in response to the TEE the first 4years of treatment, but did not change among the sites of the gradient. At the stand scale, leaf area index (LAI) decreased, and the ratios of stem SA to LAI and of fine root area to LAI both increased in trees subjected to throughfall exclusion and from the wettest to the driest site of the gradient. Taken together, these results suggest that acclimation to chronic drought in long-lived Q. ilex is mediated by changes in hydraulic allometry that shift progressively from low (branch) to high (stand) organizational levels, and act to maintain the leaf water potential within the range of xylem hydraulic function and leaf photosynthetic assimilation.

Gas exchange and leaf aging in an evergreen oak: causes and consequences for leaf carbon balance and canopy respiration (Tree Physiology, 2012)
Leaves of Mediterranean evergreens experience large variations in gas exchange rates over their life span due to aging and seasonally changing environmental conditions. Accounting for the changing respiratory physiology of leaves over time will help improve estimations of leaf and whole-plant carbon balances. Here we examined seasonal variations in light-saturated net CO2 assimilation (Amax), dark respiration (Rd) and the proportional change in Rd per 10 °C change in temperature (Q10 of Rd) in previous-year (PY) and current-year (CY) leaves of the broadleaved evergreen tree Quercus ilex L. Amax and Rd were lower in PY than in CY leaves. Differences in nitrogen between cohorts only partly explained such differences, and rates of Amax and Rd expressed per unit of leaf nitrogen were still significantly different between cohorts. The decline in Amax in PY leaves did not result in the depletion of total non-structural carbohydrates, whose concentration was in fact higher in PY than CY leaves. Leaf-level carbon balance modeled from gas exchange data was positive at all ages. Q10 of Rd did not differ significantly between leaf cohorts; however, failure to account for distinct Rd between cohorts misestimated canopy leaf respiration by 13% across dates when scaling up leaf measurements to the canopy. In conclusion, the decline in Amax in old leaves that are close to or exceed their mean life span does not limit the availability of carbohydrates, which are probably needed to sustain new growth, as well as Rd and nutrient resorption during senescence. Accounting for leaf age as a source of variation of Rd improves the estimation of foliar respiratory carbon release at the stand scale.
10.1093/treephys/tps020

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.

Leaf CO2 efflux is attenuated by acclimation of respiration to heat and drought in a Mediterranean tree (Functional Ecology, 2011)
* 1Understanding the effect of water deficit on plant respiration and its temperature sensitivity at long time-scales is important for anticipating the shift in ecosystem dynamics that is expected to occur as a result of climate change. * 2We investigated seasonal variations of leaf dark respiration and sensitivity to temperature in the upper and lower canopy of Quercus ilex trees in a forest stand that had been exposed to either 33% throughfall reduction or normal rainfall for the preceding 6 years. * 3For upper and lower canopy leaves, light-saturated photosynthesis and respiration at a reference temperature of 15 °C (R15) had the lowest values in late summer, when both traits were lower in trees subjected to throughfall reduction than in those subject to control conditions. Respiration acclimated to seasonal shifts in temperature, more intensively through summer than winter and in throughfall-exclusion than control trees. Foliar concentration of soluble sugars was positively correlated with R15 across seasons. * 4As leaf respiration decreased with increasing water deficit, and the relationship between water status and respiration did not differ between trees that had been exposed to 7 years of enhanced drought when compared with controls, we suggest that drier conditions projected for the Mediterranean may attenuate the stimulation of leaf respiratory CO2 release by global warming in Q. ilex forests.

Phenological responses to extreme droughts in a Mediterranean forest - Misson, Laurent; DEGUELDRE, DAVID; COLLIN, CHRISTIAN; RODRIGUEZ, RAQUEL; ROCHETEAU, ALAIN; OURCIVAL, JEAN-MARC; Rambal, Serge (Global Change Biology, 2011)
Mediterranean regions are projected to experience more frequent, prolonged and severe drought as a consequence of climate change. We used a retractable rainfall shelter, to investigate the impact of extreme droughts on the development of Quercus ilex leaves, flowers and fruit. In 2008, 97% of rainfall was excluded from a forest plot during the autumn, representing 50% of the 1127 mm of rain that fell during the year. In 2009, 87% of rainfall was excluded during the spring, representing 58% of the 749 mm that fell during the year. The rainfall shelter did not impact neither incident radiation nor air temperature. Autumn rainfall exclusion did not significantly affect leaf, flowers or fruit development. Spring rainfall exclusion resulted in larger and more sustained depression of leaf water potential during the key phases of foliar and floral development. Consequently, only half of the sampled trees (6) reached the shoot lengthening stage which leads to functionally mature leaves (phenophase 4), with one abandoning leaf development at budburst (phenophase 3) and the other two at the bud swelling stage (phenophase 2). All trees of the control plot passed phenophase 4, with most reaching complete leaf development. The impact of extreme droughts on flower development differed between the sexes. The spring exclusion had no effect on male flower, but only one of six trees completed female fruit maturation, compared with four in the control plot. The difference between the male and female drought impacts is likely attributable to the occurrence of male floral development before the period of lowest leaf water potential, and to the lower resource allocation requirements of male flowers. The information provided by our experimental approach may constitute a crucial step to evaluate the impact of increasing drought due to climate change on the most dominant Mediterranean tree species and to help drawing a full picture of the ecological consequences of the decline in water resource on forest dynamics under changing conditions.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate changes; Extreme events; flowering; fruiting; leaf-unfolding; rainfall changes

Is selective thinning an adequate practice for adapting Quercus ilex coppices to climate change? - Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; OURCIVAL, JEAN-MARC; Limousin, Jean-Marc; Joffre, Richard; Rambal, Serge (Annals of Forest Science, 2011)
& Introduction Future climatic scenarios demand an increasing involvement of management for forest preservation, but little is known on how forestry practices will benefit stands in facing variation of climatic components. & Objectives We investigated how selective thinning affected the response of an old Quercus ilex coppice to 6 years of throughfall reduction. Plots thinned from below (≈30% basal area removal) and unthinned plots were subject to either throughfall exclusion (TE; ≈33% throughfall reduction) or normal rainfall. Stem diameter growth, stem survival, and seed and sprout production were measured. & Results TE did not have a significant effect on stem growth but it reduced the production of viable acorns. Also, in the absence of thinning, TE accelerated the mortality of small stems and stimulated the emergence of new sprouts. Thinning reduced stem mortality, enhanced growth of residual stems, and caused a profuse emission of resprouts. Thinning also increased total seed production, but the crop had a large proportion of aborted seeds, especially in those areas subject to TE. & Conclusion The mere elimination of suppressed and diseased stems in abandoned Q. ilex coppice stands helps remaining trees to cope with current and future (probably longer and more intense) droughts. Potentially drier conditions might attenuate the success of thinning in producing a viable seed crop.
Keywords: Drought; forest adaptation strategy; seed production; sprouting; stem growth

On the differential advantages of evergreenness and deciduousness in mediterranean oak woodlands: a flux perspective - Baldocchi, Dennis D.; Ma, Siyan; Rambal, Serge; Misson, Laurent; OURCIVAL, JEAN-MARC; Limousin, Jean-Marc; Pereira, João; Papale, Dario (ECOLOGICAL APPLICATIONS, 2010)
We assessed the differential advantages of deciduousness and evergreenness by examining 26 site-years of carbon dioxide, water vapor, and energy flux measurements from five comparable oak woodlands in France, Italy, Portugal, and California (USA). On average, the evergreen and deciduous oak woodlands assimilated and respired similar amounts of carbon while using similar amounts of water. These results suggest that evergreen and deciduous woodlands have specific, and similar, ecological costs in mediterranean climates, and that both leaf habits are able to meet these costs. What are the mechanisms behind these findings? Deciduous oaks compensated for having a shorter growing season by attaining a greater capacity to assimilate carbon for a given amount of intercepted solar radiation during the well-watered spring period; at saturating light levels, deciduous oaks gained carbon at six times the rate of evergreen oaks. Otherwise, the two leaf habits experienced similar efficiencies in carbon use (the change in carbon respired per change in carbon assimilated), water use (the change in carbon assimilation per change in water evaporated), and rainfall use (the change in evaporation per change in rainfall). Overall, leaf area index, rather than leaf habit, was the significant factor in determining the absolute magnitude of carbon gained and water lost by each evergreen and deciduous oak woodland over an annual interval; the closed canopies assimilated and respired more carbon and transpired more water than the open canopies. Both deciduous and evergreen mediterranean oaks survive in their seasonally hot/dry, wet/cool native range by ensuring that actual evaporation is less than the supply of water. This feat is accomplished by adjusting the leaf area index to reduce total water loss at the landscape scale, by down-regulating photosynthesis, respiration, and stomatal conductance with progressive seasonal soil water deficits, and by extending their root systems to tap groundwater.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: carbon dioxide exchange; deciduousness vs. evergreen

Do photosynthetic limitations of evergreen Quercus ilex leaves change with long-term increased drought severity? (Plant, Cell & Environment, 2010)
Seasonal drought can severely impact leaf photosynthetic capacity. This is particularly important for Mediterranean forests, where precipitation is expected to decrease as a consequence of climate change. Impacts of increased drought on the photosynthetic capacity of the evergreen Quercus ilex were studied for two years in a mature forest submitted to long-term throughfall exclusion. Gas exchange and chlorophyll fluorescence were measured on two successive leaf cohorts in a control and a dry plot. Exclusion significantly reduced leaf water potential in the dry treatment. In both treatments, light-saturated net assimilation rate (Amax), stomatal conductance (gs), maximum carboxylation rate (Vcmax), maximum rate of electron transport (Jmax), mesophyll conductance to CO2 (gm) and nitrogen investment in photosynthesis decreased markedly with soil water limitation during summer. The relationships between leaf photosynthetic parameters and leaf water potential remained identical in the two treatments. Leaf and canopy acclimation to progressive, long-term drought occurred through changes in leaf area index, leaf mass per area and leaf chemical composition, but not through modifications of physiological parameters.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd

Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.

Modelling rainfall interception in a mediterranean Quercus ilex ecosystem: Lesson from a throughfall exclusion experiment (Journal of Hydrology, 2008)
In the Mediterranean basin, precipitation is expected to decline by the end of the 21st century as a consequence of climate change. A throughfall exclusion experiment has been established in a Quercus ilex coppice in southern France to anticipate the response of this ecosystem to a reduced precipitation amount by removing part of the throughfall. The experiment involved four 140 m 2 plots: a control plot, a throughfall exclusion plot, a thinned plot and a throughfall exclusion in a thinned plot. This experiment has been used during nearly two years to monitor throughfall amounts in the different plots. Additionally, stemﬂow has been recorded on 20 trees between 25 April 2006 and 15 May 2007. The control plot had a stem density of 6885 stems ha 1 and a leaf area index of 3.1, rainfall partitioning into interception loss, throughfall and stemﬂow was, respectively, 30.9%, 56.6% and 12.5% of the total precipitation (1605 mm over the study period). Thinning reduced the stem basal area by 33% and the total interception loss by 34.6%. Given the rainfall partitioning, the throughfall exclusion was found to remove 19% of total precipitation, which was conﬁrmed by soil water content measurements. The revised Gash analytical model predicted interception with an agreement of 6.2% of total precipitation. Results show a good transferability of the model to a plot with a different stem density, thus supporting the idea that model parameters and evaporation from a wet canopy scale linearly with canopy cover.

Isoprenoid emissions of Quercus spp. (Q. suber and Q. ilex) in mixed stands contrasting in interspecific genetic introgression (New Phytologist, 2004)
• Among oak species, Quercus ilex is classiﬁed as a monoterpene emitter and Q. suber is mainly known as a nonisoprenoid emitter. The extent and origin of this diversiﬁcation is unknown. • We examined intra- and interspeciﬁc emission variability in two mixed stands which differed in their level of hybridization and reciprocal genetic introgression based on variations in cytoplasmic (chloroplast DNA) and nuclear (allozyme) markers. • At both sites all trees identiﬁed as Q. ilex, or as recent descendants from Q. ilex × Q. suber hybrids, emitted monoterpenes. Of Q. suber trees (genetically introgressed or not by Q. ilex), 91% were also monoterpene emitters, and the remainder nonemitters. One tree identiﬁed as a Q. canariensis × Q. ilex hybrid emitted both isoprene and monoterpenes. Compared with Q. ilex, the standard emission rate of Q. suber was higher in summer and lower in autumn. Both species emitted the same monoterpenes, proportions of which showed signiﬁcant intra- and interspeciﬁc variability. • The results suggest that Q. suber populations in the French Mediterranean intrinsically emit monoterpenes, and that gene ﬂow between oak species contributes to diversiﬁcation of emission signatures.

Isoprenoid emissions of Quercus spp. (Q. suber and Q. ilex) in mixed stands contrasting in interspecific genetic introgression - Staudt, Michael; Mir, Celine; Joffre, Richard; Rambal, Serge; Bonin, Aurelie; Landais, Damien; Lumaret, Roselyne (New Phytologist, 2004)
• Among oak species, Quercus ilex is classiﬁed as a monoterpene emitter and Q. suber is mainly known as a nonisoprenoid emitter. The extent and origin of this diversiﬁcation is unknown. • We examined intra- and interspeciﬁc emission variability in two mixed stands which differed in their level of hybridization and reciprocal genetic introgression based on variations in cytoplasmic (chloroplast DNA) and nuclear (allozyme) markers. • At both sites all trees identiﬁed as Q. ilex, or as recent descendants from Q. ilex × Q. suber hybrids, emitted monoterpenes. Of Q. suber trees (genetically introgressed or not by Q. ilex), 91% were also monoterpene emitters, and the remainder nonemitters. One tree identiﬁed as a Q. canariensis × Q. ilex hybrid emitted both isoprene and monoterpenes. Compared with Q. ilex, the standard emission rate of Q. suber was higher in summer and lower in autumn. Both species emitted the same monoterpenes, proportions of which showed signiﬁcant intra- and interspeciﬁc variability. • The results suggest that Q. suber populations in the French Mediterranean intrinsically emit monoterpenes, and that gene ﬂow between oak species contributes to diversiﬁcation of emission signatures.
Keywords: basal emission rate; chemotaxonomy; chemotypes; Evergreen oaks; genetic introgression; isoprene; Monoterpenes; VOC (volatile organic compound) emissions.

An examination of the interaction between climate, soil and leaf area index in a Quercus ilex ecosystem (Ann. For. Sci., 2003)
In Mediterranean-type ecosystems, water availability is one of the most significant variables that regulates whole plant leaf area. An equilibrium should exist between climate, soil and leaf area in such water-limited conditions. The aim of this study was to identify the relations between leaf area index (LAI), environment (climate, soil) and fluxes (water, carbon) in Mediterranean evergreen oak (Quercus ilex L.) ecosystems. To achieve this objective, 50-years simulations were performed using the FOREST-BGC model by varying LAI for a reference site and for different climates and soil water holding capacities (SWC). Transpiration, drought stress, net photosynthesis and canopy water use efficiency (WUE) were examined on a yearly basis for the last ten years of the simulation. Similar to other findings, our results show that LAI depends on site water availability, including both climate (precipitation, potential evapotranspiration) and soil factors (e.g. water storage capacity). Low SWC limit the development of the ecosystem. On high SWC soils, development is mainly limited by the climate. When LAI increases under constant SWC and climate conditions, the decrease in annual transpiration per unit of LAI is accompanied by an increase in drought stress. Equilibrium LAI maximizes carbon assimilation. For the reference site, the equilibrium LAI is close to the observed value, 3.25. The corresponding transpiration, assimilation and WUE are 375 mm, 1251 g C m -2 and 3.1 mmol CO 2 mol -1 H 2O, respectively. For the different sites, there is an hyperbolic decline of WUE with increasing SWC. This implies that production efficiency per unit leaf area is higher in most water-limited environments. Our study shows that a model such as FOREST-BGC allows inter-relations between water balance, carbon balance and drought stress to be taken into account to better understand ecosystem LAI.

The key-role of topsoil moisture on CO$_2$ efflux from a Mediterranean Quercus ilex forest (Ann. For. Sci., 2003)
CO2 respiratory losses partly determine net carbon ecosystem exchanges. The main objective of this paper was to understand regulation imposed by soil water content and temperature on soil and ecosystem CO2 efflux in a holm oak (Quercus ilex L.) Mediterranean forest. Soil CO2 efflux was monitored monthly during 1999 and 2001. Moreover, experimental water treatments were conducted in 1999 over 9 small plots (0.3 m2) during nine months. Results showed strong decreases of soil CO2 efflux for a relative soil water content below 0.7. Ecosystem respiration measured by eddy covariance over a 4-year period showed strong sensitivity to soil water content and temperature. Severe limitations of soil and ecosystem efflux imposed by low values of soil water content occurred on about 90 days per year. The best adjustments of soil and ecosystem CO2 efflux were obtained using regression models where the exponential effect of temperature is linearly related to soil water content ( r2 = 0.68 and 0.79 for soil and ecosystem respectively). Our results highlighted strong differences in respiration sensitivity to topsoil moisture between soil and ecosystem. When the relative water content (RWC) is low (0.4), an increase of 1 °C provokes an increase of soil respiration of 5.7% and an increase of ecosystem respiration of 8.6%. For nonlimiting soil water conditions, at RWC = 1, the increases of respiration caused by a 1 °C temperature increase are of 8.5% and 16.5% for soil and ecosystem respectively. These results emphasized the probable determinant influences of changes in soil water regime for respiratory fluxes and net carbon exchanges of Mediterranean forest ecosystems.

Seasonal pattern of monoterpene synthase activities in leaves of the evergreen tree Quercus ilex - Fischbach, Robert Josef; Staudt, Michael; Zimmer, Ina; Rambal, Serge; Schnitzler, Jörg-Peter (Physiologia Plantarum, 2002)
Monoterpene synthase activities were measured in current year and 1-year-old leaves of holm oak (Quercus ilex L.). The monoterpene synthase activities of the leaves strongly changed with leaf development and leaf age. Enzyme activities increased rapidly in spring after leaf emergence, reaching maximum values in summer, which declined during the following winter period. In the next spring monoterpene synthase activities recovered in the old leaves to about one-third of values in the previous years and showed a similar seasonal variation as in young leaves. In both leaf age classes the pattern of enzymatic monoterpene formation was stable with α-pinene (33%), β-pinene (28%), and myrcene (26%) as prominent compounds followed by minor fractions of sabinene (10%) and limonene (3%). Monoterpene emission correlated with the activity of the synthetizing enzymes, indicating that monoterpene synthase activities in Q. ilex reflect the seasonal monoterpene emission potential of the leaves.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers accession-num: 12060257
Keywords: monoterpene emissions; monoterpene synthase activities; Quercus ilex; seasonal patterns (voyant)

Seasonal pattern of monoterpene synthase activities in leaves of the evergreen tree Quercus ilex (Physiologia Plantarum, 2002)
Monoterpene synthase activities were measured in current year and 1-year-old leaves of holm oak (Quercus ilex L.). The monoterpene synthase activities of the leaves strongly changed with leaf development and leaf age. Enzyme activities increased rapidly in spring after leaf emergence, reaching maximum values in summer, which declined during the following winter period. In the next spring monoterpene synthase activities recovered in the old leaves to about one-third of values in the previous years and showed a similar seasonal variation as in young leaves. In both leaf age classes the pattern of enzymatic monoterpene formation was stable with α-pinene (33%), β-pinene (28%), and myrcene (26%) as prominent compounds followed by minor fractions of sabinene (10%) and limonene (3%). Monoterpene emission correlated with the activity of the synthetizing enzymes, indicating that monoterpene synthase activities in Q. ilex reflect the seasonal monoterpene emission potential of the leaves.

Internal remobilization of carbohydrates, lipids, nitrogen and phosphorus in the Mediterranean evergreen oak Quercus ilex (Tree Physiology, 2001)
Remobilization of internal resources is an important mechanism enabling plants to be partly independent of external nutrient availability. We assessed resource remobilization during the growing period in woody and foliar tissues of leafy branches of mature evergreen Mediterranean oak (Quercus ilex L.) at three field sites. We compared nonstructural carbohydrates, lipids, nitrogen and phosphorus pools in leaves and stems before bud burst (March) and at the end of the growing period (July). We also experimentally defoliated leafy branches to determine the storage function of old leaves. Changes in pools of carbon compounds in leaves and stems during spring and in response to defoliation indicated that foliar and woody tissues could provide carbon to support shoot growth. Independently of stem age, soluble sugar and lipid pools decreased significantly during spring. Changes in leaf pools between March and July involved all compounds measured except starch and were accompanied by a 5%; decrease in mean leaf biomass. During the same period, 15%; of the nitrogen and 25%; of the phosphorus were removed from leaves. In contrast, woody tissues did not remobilize nitrogen or phosphorus. Our results support earlier hypotheses that leaves of evergreen species have a primary role in resource remobilization.
10.1093/treephys/21.1.9

Internal remobilization of carbohydrates, lipids, nitrogen and phosphorus in the Mediterranean evergreen oak Quercus ilex - Cherbuy, Bénédicte; Joffre, Richard; Gillon, Dominique; Rambal, Serge (Tree Physiology, 2001)
Remobilization of internal resources is an important mechanism enabling plants to be partly independent of external nutrient availability. We assessed resource remobilization during the growing period in woody and foliar tissues of leafy branches of mature evergreen Mediterranean oak (Quercus ilex L.) at three field sites. We compared nonstructural carbohydrates, lipids, nitrogen and phosphorus pools in leaves and stems before bud burst (March) and at the end of the growing period (July). We also experimentally defoliated leafy branches to determine the storage function of old leaves. Changes in pools of carbon compounds in leaves and stems during spring and in response to defoliation indicated that foliar and woody tissues could provide carbon to support shoot growth. Independently of stem age, soluble sugar and lipid pools decreased significantly during spring. Changes in leaf pools between March and July involved all compounds measured except starch and were accompanied by a 5%; decrease in mean leaf biomass. During the same period, 15%; of the nitrogen and 25%; of the phosphorus were removed from leaves. In contrast, woody tissues did not remobilize nitrogen or phosphorus. Our results support earlier hypotheses that leaves of evergreen species have a primary role in resource remobilization.
10.1093/treephys/21.1.910.1093/treephys/21.1.9
Keywords: defoliation; Growth; nutrient storage; resource remobilization

Within-tree variation in transpiration in isolated evergreen oak trees: evidence in support of the pipe model theory (Tree Physiology, 2001)
Within-tree variation in sap flow density (SFD) was measured in two isolated evergreen oak (Quercus ilex L.) trees growing in an oak savannah (dehesa) in southwest Spain. Sap flow was estimated by the constant heating method. Three sensors were installed in the trunk of each tree in three orientations: northeast (NE), northwest (NW) and south (S). Sap flow density was monitored continuously from May 18 to September 27, 1993. Daily values of SFD ranged between 500 and 4500 mm3 mm−2 day−1. There were significant differences in SFD between orientations; SFD was higher in the NE and NW orientations than in the S orientation. These differences were noted on both a daily and seasonal time scale, and were less pronounced on cloudy days and at the end of the drought period, when SFD was relatively low. Our results support the idea that branches of trees can be viewed as a collection of small independent plants.
10.1093/treephys/21.6.409

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise - Filho Teixeira, José; Damesin, Claire; Rambal, Serge; Joffre, Richard (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements
Keywords: Arbutus unedo; mixed Mediterranean woodland; Penman-Monteith equation; Quercus ilex; Quercus pubescens; sap flow; stomatal and canopy conductances

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements